2022
DOI: 10.1038/s42004-021-00619-7
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between atomically dispersed copper and phosphorous species are key for the hydrochlorination of acetylene

Abstract: Vinyl chloride, the monomer of polyvinyl chloride (PVC), is industrially synthesized via acetylene hydrochlorination. Thereby, easy to sublimate but toxic mercury chloride catalysts are widely used. It is imperative to find environmentally friendly non-mercury catalysts to promote the green production of PVC. Low-cost copper-based catalysts are promising candidates. In this study, phosphorus-doped Cu-based catalysts are prepared. It is shown that the type of phosphorus configuration and the distribution on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 67 publications
2
31
0
Order By: Relevance
“…This indicates an average valence state between Cu 1+ and Cu 2+ in both Cu-based catalysts, 61 S5). However, apart from the Cu−Cl (2.27 Å) characteristics derived from the CuCl 2 precursor, 47 Cu−O with a bond length of 1.95 Å was observed for the benchmark catalyst 15% Cu/AC, which may stem from the coordination of Cu precursors with Ocontaining groups on the support. Similarly, the slightly augmented Cu−O coordination number and the potential P− O−Cu species observed in the P 2p XPS spectrum of the 15% Cu 8 MDPO 1 /AC catalyst demonstrate that most of the Cu−O bonds still derived from the interaction of Cu species with Ocontaining groups on the support surface, and perhaps some of them stemmed from the coordination of Cu species with the O atom of the ligand.…”
Section: Catalytic Performance Evaluation Of Cu Catalystsmentioning
confidence: 93%
See 1 more Smart Citation
“…This indicates an average valence state between Cu 1+ and Cu 2+ in both Cu-based catalysts, 61 S5). However, apart from the Cu−Cl (2.27 Å) characteristics derived from the CuCl 2 precursor, 47 Cu−O with a bond length of 1.95 Å was observed for the benchmark catalyst 15% Cu/AC, which may stem from the coordination of Cu precursors with Ocontaining groups on the support. Similarly, the slightly augmented Cu−O coordination number and the potential P− O−Cu species observed in the P 2p XPS spectrum of the 15% Cu 8 MDPO 1 /AC catalyst demonstrate that most of the Cu−O bonds still derived from the interaction of Cu species with Ocontaining groups on the support surface, and perhaps some of them stemmed from the coordination of Cu species with the O atom of the ligand.…”
Section: Catalytic Performance Evaluation Of Cu Catalystsmentioning
confidence: 93%
“…Notably, the P�O stretching vibration and the inplane bending vibration of the benzene rings are red-shifted by 18 and 29 cm −1 in CuCl 2 -MDPO due to electron aggregation and electron feeding, further demonstrating the generation of a local active domain as a result of the coordination between the MDPO ligand and CuCl 2 precursors, as was verified by the appearance of peaks attributable to P−O/P−O−Cu and P−Cu species in the P 2p XPS spectrum of the 15% Cu 8 MDPO 1 /AC catalyst (Figure 4). 41,47 Structural Properties of the Cu Catalysts. The pore structure was analyzed via N 2 adsorption−desorption isotherms to determine the effect of the MDPO ligand on the texture properties of the Cu-based catalysts.…”
Section: Catalytic Performance Evaluation Of Cu Catalystsmentioning
confidence: 99%
“…Thus, the search for alternative methods to achieve the stable operation of Rubased catalysts is ongoing. 11,25 Achieving a high electron density on the Ru centers through electron transfer from Cu atoms can improve the electron complementary redox cycles, which is considered a promising stabilization strategy. 5,9,26 It has been confirmed that the high electron density of Cu can break and activate the carbon− carbon triple bond (CC) of C 2 H 2 by forming π−σ coordination bonds, thus accelerating the catalytic reaction with a lower energy barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Ru-based catalysts exhibit high activity for HCl activation, but the active sites (Ru­(III) or Ru­(IV)) are always deactivated by the induced thermodynamic autoreduction. Also, excessive reductive C 2 H 2 or HCl gas could also lead to the reduction of the Ru­(III)/Ru­(IV) pair to inactive Ru(0) species and cause coke deposition. As reported, the formation of inactive Ru(0) species occurred at any stage of the simultaneous or stepwise hydrochlorination reaction. , Thus, rationally eliminating or slowing down the generation of Ru(0) is a vital issue to improve the stability of Ru-based catalysts further. To address the problem, extensive efforts have focused on catalyst carrier design and modification of the Ru coordination environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation